Perspective: on the future of fecal microbiota transplantation - Larsen, Olaf F. A.; Brummer, Robert J. M. (Frontiers in Microbiology, 2024)
Fecal Microbiota Transplantation (FMT) has shown to possess impressive potential benefit for a wide range of clinical indications. Due to its inherent safety issues and efficacy constraints, the use of personalized FMT analogues could be a promising avenue. The development of such analogues will require a detailed understanding of their functionality, encompassing not only microbe-host interactions of the microbial taxa that are involved, but also of the ecological dimensions of the analogues and an overview of the gastrointestinal sites where these relevant microbial interactions take place. Moreover, characterization of taxa that have been lost due to diminished exposure to beneficial microbes, as a consequence of Western lifestyle, may lead to creation of future FMT analogues with the capacity to restore functionalities that we have lost.